1995
DOI: 10.1111/j.1476-5381.1995.tb14979.x
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of P2‐purinoceptors to neurogenic contraction of rat urinary bladder smooth muscle

Abstract: The contribution of P2‐purinoceptors to neurogenic contraction was investigated in rat urinary bladder smooth muscle by measurement of isotonic tension. Contraction of rat urinary bladder smooth muscle induced by electrical stimulation was decreased to 84.19±3.90% of the control (n= 16) in the presence of atropine (1 μm), which was further decreased to 38.80 ±2.75% of the control (n = 49) in the presence of both atropine and 10 μm α,β‐methylene adenosine 5′‐triphosphate (α,β‐Me ATP). The contractile response i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…␣,␤-MeATP, an ATP analog, is resistant to ATPase and selectively acts on the P2X receptor. Thus P2X receptors can be desensitized through repeated application of ␣,␤-MeATP (15). Additionally, there is always a small residual NANC component of detrusor contraction that is not mediated by either M or P2X receptors (22,56).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…␣,␤-MeATP, an ATP analog, is resistant to ATPase and selectively acts on the P2X receptor. Thus P2X receptors can be desensitized through repeated application of ␣,␤-MeATP (15). Additionally, there is always a small residual NANC component of detrusor contraction that is not mediated by either M or P2X receptors (22,56).…”
Section: Discussionmentioning
confidence: 99%
“…One possible mechanism is that ATP may act on another type of P2 receptor, but not on the P2X receptor (15). Although multiple P2X receptors have been identified in mice and human bladders, it is generally believed that P2X1 receptors are the predominant subtype involved in the neurally evoked purinergic excitatory effects (39,50).…”
Section: Discussionmentioning
confidence: 99%
“…Here we use term RB-2 to describe the antagonistic actions of the mixture of terminal ring meta-and para-sulfonate, and we discuss separately the allosteric actions of Cibacron blue 3GA, the purified ortho isomer, at recombinant P2XRs. The antagonistic actions of RB-2 were observed in several diverse ATPmediated physiological responses, such as rat urinary bladder smooth muscle contraction (Hashimoto and Kokubun, 1995), rat cecum inhibitory junction potentials (Manzini et al, 1986), and calcium influx in rat parotid acinar cells (Soltoff et al, 1989). It has also been suggested that RB-2 inhibits ectonucleotidase activity in X. laevis oocytes and ATP-induced inflammation of the mouse hind paw .…”
Section: A P2x Receptor Agonism and Antagonismmentioning
confidence: 98%
“…When cholinergic and purinergic components of EFSinduced contractile responses of detrusor smooth muscles were abolished, there remained a considerable amount of contraction (33% in NC group, 35% in HC group). Incomplete desensitization of P2X purinoceptors or the presence of other purinoceptors in the rat detrusor smooth muscle (24,33) could be involved in the residual contractile component together with the other NANC transmitter(s) released (18,(34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%